ANALISIS FAKTOR PENYEBAB TERJADINYA RUPTUR PERINEUM PADA IBU BERSALIN - Indah Sari; Suprida; Yulizar; Titin Dewi Sartika Silaban (Jurnal Kesehatan dan Pembangunan, 2023)
Pregnancy danger signs are symptoms that indicate the mother or baby is in danger. Pregnant women who do not do the examination, then it will not be known whether the pregnancy is going well, experiencing a high risk or obstetric complications that can endanger the life of the mother and fetus, so as to increase morbidity and high mortality. The purpose of the research was to find out the relationship of maternal age, parity, pregnancy distance, history of preterm labor, and simultaneous preeclampsia to high-risk pregnancies at Gunung Megang Public Health Center in 2021.This research is an analytical survey study, with a cross sectional design. The population in the study was 572 pregnant women. Large samples using the formula Slovin so that 86 pregnant women were obtained with purposive sampling techniques. Examination of factors related to high risk pregnancy using a check sheet and looking at medical records data Puskesmas. Assessment of the relationship of factors that are related to high-risk pregnancy using the Chi-square test.The results of the Chi-square test showed that there was a relationship in maternal age (p=0.004), parity (p=0.018), pregnancy distance (p=0.010), history of preterm labor (p=0.005) and preeclothes (p=0.016) with high-risk pregnancies.